IMPLEMENTING COMMUNICATIVE LANGUAGE TEACHING METHOD IN ESL CLASSROOMS - Rakhmonova, Dilshoda (Educational Research in Universal Sciences, 2023)
Communicative Language Teaching (CLT) has become a widely accepted methodology for teaching English as a Second Language (ESL) over the past few decades. However, the practical implementation of CLT presents several challenges in many classroom contexts. This paper discusses the key principles of CLT and addresses common obstacles faced by ESL teachers when adopting this approach. It provides suggestions for overcoming challenges related to transitioning from teacher-centered to learner-centered practices, developing authentic learning materials, establishing a low-anxiety environment, conducting formative assessment, and managing large class sizes. The paper argues that with proper understanding, planning and context-specific adaptations, CLT can be effectively implemented to develop students’ communicative competence despite resource constraints.